Efficacy of Three Povidone Iodine Formulations against Cutibacterium acnes Assessed through In Vitro Studies: A Preliminary Study - Maxime Pichon; Christophe Burucoa; Victor Evplanov; Filippo Favalli (MDPI AG, 2022)
Cutibacterium acnes (C. acnes, formerly known as Propionibacterium acnes) is the major causative agent of prosthetic joint infections (PJI). Treatment of PJI with antibiotics is difficult due to antibiotic resistance and adverse side effects on patients' health. Proper disinfection of the surgical site using a variety of povidone iodine formulations could prevent C. acnes infection. In the current study, the efficacy of the three povidone iodine (PVP-I) formulations, viz: PVP-I 10% dermic solution, PVP-I 5% alcoholic solution and PVP-I 4% scrub, was tested against C. acnes, in vitro, in the presence of interfering substances mimicking soiling conditions. C. acnes strain ATCC 6919 was used to test the bactericidal activity of the povidone iodine formulations according to the modified dilution-neutralization method described in French Norm EN standard 13727. A 3-log reduction in the bacterial cell count in 60 s was considered to be significant. The results showed that under experimental conditions, the three PVP-I formulations displayed bactericidal activity against the micro-organism, Cutibacterium acnes, and that the lowest concentration of povidone-iodine active against C. acnes was 0.4%. These results are encouraging as PVP-I offers a low-cost and efficient method of disinfection.